(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract: The research problem was represented in the role of the external auditor in limiting earnings management The research aims to test this effect on the economic units operating in the Iraqi business environment The researcher relied on applying a model, analyzing the data of the financial statements published in the Iraq Stock Exchange for the research sample from the different economic sectors for the year (2020-2021) according to the (miller) model. Through his study, the target community of this survey is the external auditors, audit offices and auditors of the federal audit bureau, and the researcher used a set of statistical analysis for the sample questionnaire form consisting of (89) individuals distributed between the financial Dome Bureau and audit offices. Through the study, the researchers have reached a set of results, the most important of which are: Profit management is often a process of manipulating accounting figures by exploiting opportunities to get rid of compliance with accounting rules, measurement alternatives and disclosure applications to transfer financial statements from what they should be to what the preparer of these statements prefers. Therefore, it is necessary to meet him from the other side of the observers, whether in the audit offices or the observers of the Financial Control Bureau, to be at the same level, if not higher, in order to detect and limit these practices so that he can reach to provide reasonable assurances that these financial reports are free of any deviations, manipulations or fraud.